(untitled) (Práxis Educativa, 2009)
This paper uses the concept of discourse to contrast some of the ways in which ’the teacher’ is positioned and constructed within recent reform policies in the UK and the USA. In other words, how is the role and purpose of the teacher articulated differently and what are the implications of these different articulations for the work relationships, self-perception and effectivity of the teacher? It also draws attention to the wider meanings and possible implications of these attempts at reforming and restructuring educational provision and identifies a set of significant discursive differences between UK and US school reforms. Further, it begins to explore the implications of these reform attempts for teacher’s work, as well as some of the ways in which ’the teacher’ is conceptualised differently in each case. The paper draws on the work of Michel Foucault and theories of discourse. Keywords: Teachers’ work. Discourse. Educational reforms.